Mediastinoscopy Under Local Anesthesia—A Valuable Diagnostic Technique - Ward, Paul H. (1970)
Mediastinoscopy is an important, new endoscopic diagnostic technique. The simplicity of the technique and low morbidity and mortality associated with the procedure when carried out under local anesthesia suggest that in many instances mediastinoscopy for direct visualization and excision of biopsy specimens may replace diagnostic thoracotomy in many cases.